Description of the immature stages of Sigara (Tropocorixa) santiagiensis (Hungerford, 1928) (Insecta: Heteroptera: Corixidae) - Konopko, Susana Amanda (2013)
The immature stages of Sigara santiagiensis are described and illustrated for the first time. The eggs of Sigara can be distinguished by the chorionic surface. The main characters separating the five nymphal instars of S. santiagiensis are: body and head lengths; body, head and eye widths; ocular index; numbers of transverse sulcations of the rostrum, setae on the inner surface of protibiotarsus, campaniform sensilla on posterior surface of protrochanter, spines on posteroventral surface of mesotibia and on tibial comb of metaleg, long, slender setae on posterodorsal surface of mesotarsus, spines and swimming hairs on anteroventral and posterodorsal surfaces of metatarsus; and grade of development of the wing pads. The body length, the chaetotaxy of the mesonotum, profemora and metafemora, protibiotarsus, metatibia, metatarsus and urosternites distinguish species or group of species of instars I and V of some of the species of the genus Sigara described up to now.